Pengembangan Kemampuan Numerasi Siswa Melalui Media Permainan Edukatif di SDN 069/VI Talang Tembago: Studi Kualitatif - Roni Agustina; Bodi Kurniawan (Master Qualitative Research in Education, 2026)
Numeracy skills are one of the fundamental competencies that elementary school students must possess to support academic success and daily life activities. However, numeracy learning often faces various challenges, such as low student interest in learning, monotonous teaching methods, and limited use of engaging instructional media. This study aims to describe the development of students’ numeracy skills through the use of educational game media at SD Negeri 69/VI Talang Tembago. The research employed a qualitative approach with a descriptive method. The participants consisted of the school principal, classroom teachers, and students of SD Negeri 69/VI Talang Tembago. Data were collected through observation, interviews, and documentation. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings revealed that the use of educational game media increased students’ engagement in numeracy learning, enhanced learning motivation, and helped students understand mathematical concepts in a more concrete and enjoyable way. Educational games also promoted social interaction, collaboration, and critical thinking skills among students. Therefore, educational game media can be considered an effective alternative for developing numeracy skills in elementary school students